DNA Microarray Profiling Highlights Nrf2-Mediated Chemoprevention Targeted by Wasabi-Derived Isothiocyanates in HepG2 Cells - Trio, Phoebe Zapanta; Kawahara, Atsuyoshi; Tanigawa, Shunsuke; Sakao, Kozue; Hou, De-Xing (Nutrition and cancer, 2017)
6-MSITC and 6-MTITC are sulforaphane (SFN) analogs found in Japanese Wasabi. As we reported previously, Wasabi isothiocyanates (ITCs) are activators of Nrf2-antioxidant response element pathway, and also inhibitors of pro-inflammatory cyclooxygenase-2. This study is the first to assess the global changes in transcript levels by Wasabi ITCs, comparing with SFN, in HepG2 cells. We performed comparative gene expression profiling by treating HepG2 cells with ITCs, followed by DNA microarray analyses using HG-U133 plus 2.0 oligonucleotide array. Partial array data on selected gene products were confirmed by RT-PCR and Western blotting. Ingenuity Pathway Analysis (IPA) was used to identify functional subsets of genes and biologically significant network pathways. 6-MTITC showed the highest number of differentially altered (≥2 folds) gene expression, of which 114 genes were upregulated and 75 were downregulated. IPA revealed that Nrf2-mediated pathway, together with glutamate metabolism, is the common significantly modulated pathway across treatments. Interestingly, 6-MSITC exhibited the most potent effect toward Nrf2-mediated pathway. Our data suggest that 6-MSITC could exert chemopreventive role against cancer through its underlying antioxidant activity via the activation of Nrf2-mediated subsequent induction of cytoprotective genes.